Предмет:
МатематикаАвтор:
alissawang1/2(3а-8)-1/3(2b+9) = 6,6
0,5*3a-0,5*8 - 0,3*2b+0,3*9 = 1,5a-4 - 0,6b+2,7
1,5a-4-0,6b+2,7 = 1,5a-4+2,7-0,6b = 1,5a-1,3-0,6b
Выражение 1,5a-1,3-0,6b при a = , b =
1,5*-1,3-0,6*
=
1)
2) 8-1,3 = 6,7
3)
4) 6,7-0,1 = 6,6
Ответ: 6,6.
Автор:
victoralexanderДобавить свой ответ
Предмет:
Английский языкАвтор:
mikaylamorenoОтветов:
Смотреть
Предмет:
МатематикаАвтор:
carpenterОтветов:
Смотреть
Предмет:
ИсторияАвтор:
jessiepatrickОтветов:
Смотреть
Предмет:
МатематикаАвтор:
eddiemilesОтветов:
Смотреть